Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,435 questions

17,804 answers

1,438 comments

157,633 users

Can anyone help me with any of these and show me how you did them so I can learn, pleasee? Thanks!

0 votes

Let f(x) = x + 7 and g(x) = x – 2. What is f(x) • g(x)?

x^2 – 5x + 14

x^2 + 5x – 14

x^2 + 5x – 5

x^2 + 9x + 5

What is the quotient: (3x^3 – 16x^2 + 23x – 6) ÷ (3x – 1) ?

x^2 + 5x + 6

x^2 – 5x + 6

–x^2 – 5x – 6

–^x2 + 5x + 6 

asked Jun 29, 2013 in ALGEBRA 1 by angel12 Scholar

2 Answers

0 votes

Let f(x) = x + 7 and g(x) = x - 2

Then f(x) * g(x) = (x + 7) * (x - 2)

This is in the form (a + b) (c - d) where a = x, b = 7, c = x and d = 2

                           = x*x - x*2 + 7*x - 7*2                     [ Since (a + b) (c - d) = ac - ad + bc - bd ]

                           = x^2 - 2x + 7x - 14                          [ Since a*a = a^2 ]

                           = x^2 + 5x - 14

Therefore the answer is x^2 + 5x - 14

answered Jun 29, 2013 by joly Scholar
0 votes

Quotient of (3x^3 - 16x^2 + 23x - 6) / (3x - 1) can be odtained by using synthetic division.

3x - 1 can be written as x - 1/3

             1/3   |    3     -16     23     -6

                     |     0       1      -5      6

                     |________________

                           3    -15    18     |0

=> 3x^2 - 15x + 18                      [ dividing by 3 ]

=> x^2 - 5x +6

Therefore the answer is x^2 - 5x + 6.

answered Jun 29, 2013 by joly Scholar

Related questions

...